Morphological Changes in the Gastric Mucosa of Adult Female White Outbred Rats Caused by the Action of Anti-Inflammatory Drugs - Norbekovich , Toshmamatov Bakhtiyor; Eshmamatovna , Djumanova Nargiza; Sirojiddinovna , Sirojiddinova Munojat (American Journal of Bioscience and Clinical Integrity, 2025)
Therefore, it is critical to have systems in place to ensure that medications are only started when indicated, that patients are fully informed of the benefits and potential complications of treatment, and that patients are regularly reviewed to ensure compliance with their medication regimen.Although treating patients with complex medical problems with the right medications can improve clinical outcomes, quality of life, and life expectancy, the risk of adverse drug reactions due to polypharmacy increases, in some cases leading to hospitalization and even death.